Asynchronous Adaptive Delay Tolerant Index Cache Using In-memory Delta Cell - Ma, Kun; Yang, Bo (Informatica, 2015)
Relational database indexes, used to speed up access to data stored in a database, are maintained when data in the source table of the index is modified. Therefore, relational database index management can involve time consuming manual analysis and specialized development efforts, and impose organizational overhead and database usage costs, especially in the context of big data. To address this limitation, this paper proposes an asynchronous adaptive delay tolerant index cache using in-memory delta cell. The contributions of index cache are adaptive management and fine-grained delta cell. Finally, our experimental evaluation shows that this simple index cache has the features such as update efficiency with frequent changes, transparency to developers, and low impact on database performance.